Change management a case study for change through the color print code - Samson, Lourdes K. (2008)
This paper is a case study in change management of a 7-year old institution for primary and secondary education catering to all girls predominantly of Filipino-Chinese descent. It identified five sets of change agents by using the color code for change agents developed by Caluwe and Vermaak. The five color tags represent different perceptions and attitudes towards change. Using a questionnaire, it was found that the organization favors a Green Code which encourages the culture of an open learning organization. This means that learning situations are set up in which people give and receive feedback continuously and experiment with effective ways of acting. The research indicates a predominant color among the five groups which allows a change to be more focused and consistent in its approach.